Workshop Implementasi Kurikulum Merdeka Di Pondok Pesantren DDI Galesong Baru Makassar - Hardianto Rahman; Ahmad Syawaluddin; Latri Latri; Muhammad Faisal; Bahar Bahar (Universitas Negeri Makassar, 2023)
Islamic boarding schools play a central role in character education and the instillation of religious values in Indonesia. In the context of the Merdeka Curriculum, they hold great potential for integrating religious values with a broader curriculum, producing graduates who are skilled, ethical, and make positive contributions to society. The Implementation Workshop of the Merdeka Curriculum is conducted by delivering both theoretical and practical aspects through the Independent Learning Flow method developed by the Ministry of Education and Culture. The steps in the Independent Learning Flow used include: 1) self-awareness, 2) concept exploration, 3) collaborative space, 4) contextual demonstration, 5) understanding elaboration, 6) interconnection of materials, and 7) real action.The results of implementing the Merdeka Curriculum using the Independent Learning Flow demonstrate significant achievements with an implementation percentage of 86.79%. Each step in the flow contributes significantly to the overall implementation, creating a learning environment focused on active student engagement and the application of Merdeka Curriculum principles.